Assessing the impact of urban transformations on exposure to air pollutants in the city of Bogota : a cable-car implementation and renewal of the BRT system fleet (2020)
Assessing personal exposure to air pollutants in large cities has gained notoriety and relevance as commuters are often exposed to higher concentration than those reported by central monitoring sites. Urban development and the built environment can have substantial effects on personal exposure. Between 2018 and 2019 in Bogota, a cable car was built in the south of the city connected to the bus rapid transport system (BRT). Simultaneously, a new bus fleet replaced almost 1400 18years-old diesel buses. In this work, we analyzed the potential impacts of these two urban transformations on personal exposure. For this, 136 personal exposure measurement sessions spanning 540 hours were carried out. A 50% decrease was observed in the concentrations where a decrease from 176 to 92 æg-m3, from 90 to 45 æg-m3 and from 4.8 to 3.3 ppm of PM2.5, eBC and CO respectively was observed after the process of fleet renewal...